The Most Frequent Values of the Largest Prime Divisor Function. Issue 2 (3rd April 2017) - McNew, Nathan
ABSTRACT: We consider the distribution of the largest prime divisor of the integers in the interval [2, x ] and investigate in particular the mode of this distribution, the prime number(s) which show up most often in this list. In addition to giving an asymptotic formula for this mode as x tends to infinity, we look at the set of those prime numbers which, for some value of x, occur most frequently as the largest prime divisor of the integers in the interval [2, x ]. We find that many prime numbers never have this property. We compare the set of "popular primes, " those primes which are at some point the mode, to other interesting subsets of the prime numbers. Finally, we apply the techniques developed to a similar problem which arises in the analysis of factoring algorithms.